Piodermitis. Estudio bacteriano en dos hospitales pediátricos. - Zuazo Silva, Jorge L.; Labarrere Sarduy, Nidia E.; Portuondo de Castro, Rita; Suárez Cabrera, María (Revista Cubana de Pediatría, 2023)
Conocer la frecuencia de infección y enfermedad estreptocócica en este medio.